2015
DOI: 10.1097/sap.0b013e3182956632
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Speech Outcomes Using Radical Intravelar Veloplasty or Furlow Palatoplasty for the Treatment of Velopharyngeal Insufficiency Associated With Occult Submucous Cleft Palate

Abstract: Nonsyndromic patients with hypernasal speech are treated effectively and safely with either IVV or FP. Intravelar veloplasty trended toward lower speech scores than FP (76% IVV, 58% FP PWSS absolute reduction). Syndromic patients with OSMCP may be more effectively treated with FP (72% IVV vs 79% FP PWSS absolute reduction). Intravelar veloplasty is associated with shorter operative times. Both techniques are associated with low morbidity, improved speech scores, and low reoperative rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 7 publications
0
17
0
1
Order By: Relevance
“…Phonology and language data reported in Schönweiler et al's () study were also excluded as they were grouped with other forms of orofacial clefting and not specific to SMCP. In two studies, nonsyndromic and syndromic cases were in the same experimental group; however, individual participant data were reported, enabling relevant nonsyndromic data to be extracted (Afrooz et al, ; Oji et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Phonology and language data reported in Schönweiler et al's () study were also excluded as they were grouped with other forms of orofacial clefting and not specific to SMCP. In two studies, nonsyndromic and syndromic cases were in the same experimental group; however, individual participant data were reported, enabling relevant nonsyndromic data to be extracted (Afrooz et al, ; Oji et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Evidence supporting the impact of surgery type on postoperative speech outcomes was mixed (Afrooz et al, ; Calis et al, ; Ezzat et al, ; Park et al, ). Afrooz et al () and Ezzat et al () reported no significant difference in postoperative velopharyngeal functioning between (a) radical intravelar veloplasty and modified Furlow palatoplasty; and (b) radical intravelar veloplasty and V–Y pushback pharyngoplasty with intravelar veloplasty, respectively. Park et al () found no significant difference in postoperative articulation between those who received a pushback palatoplasty, pharyngeal flap, pushback with pharyngeal flap, or Furlow palatoplasty.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, another recent retrospective review evaluated the safety and efficacy of radical intravelar veloplasty (group 1, 18 patients) versus Furlow palatoplasty (group 2, 17 patients) in the treatment of 35 patients with VPD and occult submucous cleft palate [16]. Patients were assigned on rotating schedule to either a surgeon who performed radical intravelar veloplasty or one who performed Furlow palatoplasty.…”
Section: Furlow Palatoplastymentioning
confidence: 99%